PNGase H + variant from Rudaea cellulosilytica with improved deglycosylation efficiency for rapid analysis of eukaryotic N‐glycans and hydrogen deuterium exchange mass spectrometry analysis of glycoproteins. (2nd September 2022) - Guo, Rui‐Rui; Zhang, Tian‐Chan; Lambert, Thomas Ole Tandrup; Wang, Ting; Voglmeir, Josef; Rand, Kasper D.; Liu, Li
Abstract : The analysis of glycoproteins and the comparison of protein N ‐glycosylation from different eukaryotic origins require unbiased and robust analytical workflows. The structural and functional analysis of vertebrate protein N ‐glycosylation currently depends extensively on bacterial peptide‐N4‐( N ‐acetyl‐ β ‐glucosaminyl) asparagine amidases (PNGases), which are indispensable enzymatic tools in releasing asparagine‐linked oligosaccharides ( N ‐glycans) from glycoproteins. So far, only limited PNGase candidates are available for N ‐glycans analysis, and particularly the analysis of plant and invertebrate N ‐glycans is hampered by the lack of suitable PNGases. Furthermore, liquid chromatography–mass spectrometry (LC–MS) workflows, such as hydrogen deuterium exchange mass spectrometry (HDX‐MS), require a highly efficient enzymatic release of N ‐glycans at low pH values to facilitate the comprehensive structural analysis of glycoproteins. Herein, we describe a previously unstudied superacidic bacterial N ‐glycanase (PNGase H + ) originating from the soil bacterium Rudaea cellulosilytica (Rc), which has significantly improved enzymatic properties compared to previously described PNGase H + variants. Active and soluble recombinant PNGase Rc was expressed at a higher protein level (3.8‐fold) and with higher specific activity (~56% increase) compared to the currently used PNGase H + variant from Dyella japonicum (Dj). Recombinant PNGase Rc was able to deglycosylate the glycoproteins horseradish peroxidase and bovine lactoferrin significantly faster than PNGase Dj (10 min vs. 6 h). The versatility of PNGase Rc was demonstrated by releasing N ‐glycans from a diverse array of samples such as peach fruit, king trumpet mushroom, mouse serum, and the soil nematode Caenorhabditis elegans . The presence of only two disulfide bonds shown in the AlphaFold protein model (so far all other superacidic PNGases possess more disulfide bonds) could be corroborated by intact mass‐ and peptide mapping analysis and provides a possible explanation for the improved recombinant expression yield of PNGase Rc.